'Ararat' and the politics of 'preserving' denial - Daldal, Asli (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2007)
Daldal analyses Atom Egoyan's film Ararat (2002) in terms of its 'truth claims' and its ostensible critique of the politics of denial of the Turkish authorities. Her essay is not an apologia for Turkish attitudes but claims that, while searching for the 'truth' amid denial and deception, the film creates its own 'official history', which is presented as the history, mostly based on nostalgia and 'post-memory'. The Armenian diaspora still relies heavily on the genocide in order to build consciousness and cohesion, and Ararat contributes further to the need for sacred codes, sacred lands and sacred myths. Although the Turkish denial of the genocide is unacceptable, by demonizing the Turks and Turkey, the film contributes to the preservation of that denial, which has been helpful in the creation of diasporic Armenian identity.
Keywords: Ararat; Armenian genocide; Atom Egoyan; denial; genocide; post-memory; Turkey; Arts & Humanities - Other Topics; Ethnic Studies